CHANGES TO THE CONCESSION CONTRACT IN THE EUROPEAN UNION LAW - Divljak, Drago (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
The subject of legal analysis in the paper is a narrow, but very important and specific legal segment, namely the change of the concession contract during its validity. The consideration is based on the analysis of the relevant secondary EU law, with the appropriate use of practice of the Court of Justice of the EU. The ultimate goal was to evaluate the situation of the current EU law, both at the conceptual plan, and in details. The emphasis was in the nature, scope and conditions for changes to the contract and their implications. The paper concludes that the legal regulating of the changes to the concession contract is not an easy task for the regulator. In particular having in mind that this contract cannot be seen only through the prism of internal legal relations between the concession participants, without implications for the third persons and other interests. In such a context the optimum regulating of changes to the concession contract requires a layered legal architecture, mutually coherent, sufficiently clear and predictable, and yet relatively flexible. In that respect, the Directive 2014/23EU, manages to meet the given requirements up to the highest extent in methodological sense and both in terms of regulating and in terms of content. However, due to its generality, most of the given regulation will require specifying through national regulations in the EU Member States, and primarily in the practice of the Court of Justice of the EU. This primarily refers to significant changes to the concession contract.